Intersectional subaltern counterpublics: UndocuQueer online activism and testimonios - Galta, Sandra Y. (Kansas State University, 2018)
In this study, I investigate UndocuQueer activists and their use of social media as one type of subaltern counterpublic. Subaltern counterpublics are spaces marginalized communities forge to center their voices and experiences. These counterpublics represent aggregations of emancipatory agency and stand as responses to their exclusion or marginalization by the dominant public sphere. UndocuQueer activists strategically engage in the public sphere using social media because it grants them momentum and brings national attention to their agenda. In this research, I use an interdisciplinary and intersectional approach to understand the UndocuQueer social movement. The guiding research questions were: 1) How do UndocuQueer activists create subaltern counterpublics? 2) How do UndocuQueer activists present their multiple and complex identities on Twitter? Using critical discourse analysis of Twitter, I coded and analyzed over 600 tweets. To further this analysis, I used critical Xicana feminist standpoint to gather three testimonios of UndocuQueer activists. The major findings are of this project are: 1) the UndocuQueer subaltern counterpublic formed through the state’s anti-immigrant policies and the public sphere’s marginalizations and misrepresentations. 2) the UndocuQueer community forged an intersectional subaltern counterpublic online through their lived experiences as undocumented and queer. 3) the undocu-movements: UndocuQueer, UndocuTrans, UndocuBlack, UndocuAPI, and UndocuSolidarity operate coalitionally; thus, I call this a coalitional intersectional subaltern counterpublic. 4) the UndocuQueer activists use social media for community, expression and support of art, and organizing. 5) Lastly, UndocuQueer activists engage in multiple forms of activism via social media, such as participating in marches and civil disobedience and sharing events, workshops, petitions, and donation pages. Overall, this study provides a rich description of how marginalized communities, especially those of the UndocuQueer community, have great agency despite their precarious situation: a counter narrative that is usually unexposed. This project finds how the UndocuQueer community face multiple marginalizations and exclusions from the state through its anti-immigrant policies, the public sphere through its misrepresentations in the media, from LGBTQ communities and organizations, and from Latinx and immigrant communities. I show how the UndocuQueer’s intersectional and coalitional subaltern counterpublic forged online as a safe haven for themselves and to engage with the public sphere. With this information, we have find better ways to be their allies, support them, and listen to their calls to action.
Keywords: Subaltern counterpublics; Intersectionality; Social media; Social movements; UndocuQueer activists; Twitter activism